“We can make it better you and I” : How Ugandan girls raised awareness of sexual and gender related violence - Macnab, Andrew John; Besigye, Innocent; Tusubira, Brenda (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Sexual and gender related violence (SGRV) against girls is a dark stain on the fabric of life and the most pervasive breach of human rights worldwide. In spite of laws to combat violence, weak enforcement and discriminatory social norms remain significant problems globally, and urgent action employing ‘novel and innovative’ solutions is called for by the World Health organization and United Nations International Children’s Fund. Using knowledge of African society gleaned from work in school-based health promotion programs in Uganda we engaged girls, gave them a voice, and raised national awareness about the impact of SGRV through a celebrity recorded music video that highlighted the SGRV priorities the girls identified. While the unique power of the combination of images, illustrative scenarios, lyrics and music in the video engaged and informed, still photographs were also integral to the success of this call from girls ‘to make things better”. Our photographic record of this project captured many ethnographic elements of this initiative during its creation; selected images were central to the success of the promotional campaign to disseminate the messaging of the video nationwide; sharing photographs helped to maintain the engagement of team members, especially those unable to be in Uganda; and, our image archive provides a uniquely valuable element for knowledge transfer of ‘what worked and why’ in this initiative. Received: 16 October 2024 | Revised: 09 November 2024 | Accepted: 15 November 2024.